Virtual Currency Accounting: Suggested Models - BENAOUALI , Djilali; BELMECHRI , Bouchra (Journal of Research in Finance and Accounting, 2020)
This study aims to clarify the importance of virtual currencies due to the increasing of using it in transactions between people without a broker, and these currencies are characterized that they are not controlled by any central bank, and using it in transactions poses a challenge to accounting. The study concluded that the accounting standards issuing bodies conducted studies on the accounting of operations conducted through virtual currencies, such as the proposal of the Accounting Standards Board of Japan for a standard project, which included a model of how to record the required disclosures of the moneychanger of these currencies.